Akademisyenlerin Gözünden Sporda Sosyal Alanlardaki Yöntem Yaklaşımlarının İrdelenmesi - (:unkn) unknown (My University, 2018)
Amaç: Sporda sosyal alanlarda, farklı çalışmalarla ortaya çıkarılan nicel araştırma yöntemlerininyoğunluğunu alanda çalışma yapan akademisyenlerin gözünden incelemektir. Buyolla nicel araştırma yöntemlerinin baskın yöntem olarak kullanılmasının sebepleri anlaşılmayaçalışılmaktadır. Gereç ve Yöntemler: Sporda sosyal alanda araştırma yapan akademisyenlerindüşünce ve deneyimlerini derinlemesine anlamak için nitel araştırma yöntemi benimsenmiştir.Araştırmaya en az beş yıldır sporda sosyal alanlarda araştırma yapan, ulusal ve uluslararası bilimselmakaleleri olan 19 akademisyen katılmıştır. Veri toplamada yapılandırılmış/açık uçlu soruformu katılımcılara kurumsal e-posta adresleri üzerinden ulaştırılmıştır. Veriler içerik analiziyleanaliz edilmiş; açık ve tematik kodlama yapılarak temalar belirlenmiştir. Bulgular: İçerikanalizi sonucunda “pozitivist nicel yöntem geleneği” ve “araştırma yöntemlerine ilişkin algılar”olmak üzere iki tema ortaya çıkmıştır. Pozitivist nicel yöntem geleneği teması altında a) Kurumsalekol ve eğitim yaklaşımı, b) Yöntem popülaritesi, c) Danışman yaklaşımı alt temaları;araştırma yöntemlerine ilişkin algılar teması altında ise a) Kolay(cı)lık/sonuca çabuk ulaşma, b)Uzun, yorucu ve zahmetli nitel veri süreci, c) Artan nitel yöntem kullanımı alt temaları belirlenmiştir.Sonuç: Araştırma sonucunda, nicel araştırma yöntemli yaklaşımın sıklıkla kullanılmasınınardında pozitivizm temelli araştırma yöntemlerinin benimsenmesinin yattığı veçalışmalarda yöntem tercihinin belirlenmesinde çok farklı bireysel ve kurumsal sebeplerin önemlirol oynadığı görülmektedir.

Objective: The aim of this study was to question the dominance of quantitative research methods in sport in social studies through eyes of researchers. For this purpose, the study aimed to understand the rationales of dominance in quantitative studies. Material and Methods: 19 experienced researchers are involved to the study who could provide insightful information about the subject. The inclusion criterion was to involve researchers who have contributed to the field by publishing national and international articles in the last 5 years. Data was collected through sending structured/open-ended interview questionnaires to institutional e-mail addresses of the researchers. Content analysis method was used in the data analysis and themes were generated with open and thematic coding processes. Results: After data analysis, two main themes, “tradition of positivist quantitative method” and “perceptions regarding research methods” was obtained. Subthemes that are a) Institutional tradition and educational understanding, b) Popularity of method, c) Perspective of supervisor were determined under the tradition of positivist quantitative method theme. Subthemes that are a) Cutting corners, b) Measurability/quantification, c) Long, tiring and onerous data process were composed under the perceptions regarding research methods theme. Conclusion: The results showed that embracement of positivism-based research method lied behind the dominant use of quantitative research methods. However, it was seen that beliefs regarding the easiness of quantitative research method, carrying through in a short time, and requirement of an effortful data process in qualitative research method has also played a significant role in the determination of method choices.
Questioning Research Method Approaches in Social Fields of Sports Sciences Through Eyes of Researchers in Turkey
Keywords: Davranış Bilimleri; Eğitim, Eğitim Araştırmaları